PTS Chemistry Question Points Class X MIPA-1 Difficulty Analysis in Online Learning (2019/2020) in SMA 10 Bengkulu City - R.Pan R.Pan; Alek Sudarmanto; Windy Otaviannissa; Ahmad Walid (Universitas Lampung, 2021)
Abstract: PTS Chemistry Question Points Class X MIPA-1 Difficulty Analysis in Online Learning (2019/2020) in SMA 10 Bengkulu City. The purpose of this study is to assess the appropriateness of the level of difficulty of semester assessment questions in Chemistry class X MIPA-1 at SMA 10 Kota Bengkulu. The descriptive method was used in the research, and data was collected in this study through documentation, interviews, and question items. This study analyzes the data collected using the formula to determine the level of difficulty of the question and is based on the results of the analysis of the question given by the teacher of Chemistry class X MIPA-1. The details of the questions given fall into the category of difficult questions when viewed from the level of difficulty. It can be seen that 17 children (53.125 % ) have difficult questions, 7 children (21.875 % ) have moderate questions, and 8 children (25 % ) have easy questions. Keywords: Analysis, Problem Difficulty Level, Chemistry Lessons.